ESTRESSE TÉRMICO E MORFOGÊNESE IN VITRO DE SEMENTES DE Dalbergia nigra - Simões, Ingridh Medeiros (2021)
The species Dalbergia nigra (Vell.) Allemão ex Benth is popularly known as jacaranda from Bahia, it has wood used for the manufacture of luxury furniture and civil constructions, a factor that included it in the Official List of the Endangered Brazilian Flora due to its sharp exploitation. Little is known about the propagation of this species, and tissue culture may be an important allied technique for the production of largescale seedlings of this species. The objective of this study was to study the physiological and biochemical characteristics of Dalbergia nigra seeds under heat stress in vitro, as well as their morphogenesis using different explants under cytokinetic combinations. Chapter I: Physiological and biochemical quality of Dalbergia nigra seeds under heat stress in vitro at 45 ° C for different hours (0; 24; 48; 72; 96). Physiological analyzes of moisture, electrical conductivity, germination speed index, normal and abnormal seedlings, root and hypocotyl shoot length, collar diameter, shoot and root dry mass and Dickson quality index were performed and biochemical analysis of total carbohydrates, total lipids, total phenols, total proteins, starch and fibers. The statistical analyzes consisted of Pearson's regression and correlation. There was a decrease in germination and vigor with the hours of thermal stress, with a decrease from 95 to 0%, with 0 and 96 hours respectively and a reduction in the content of carbohydrates, lipids and proteins. Chapter II: In vitro morphogenesis of hypo and epicotyledon explants of Dalbergia nigra, induced by cytokinetic combinations. The number of shoots, number of leaves, shoot length, stem diameter, root number, root length, dry mass of the shoot and dry mass of the root were analyzed. The statistical analyzes consisted of Tukey's means test and Pearson's correlation (p <0.05). The use of 6-benzylaminopurine (BAP - 2.22 µM) in the multiplication of shoots provided a high multiplication factor, length and dry mass of shoots, number, length and dry mass of root, when associated with the explant cotyledon node.